Salmonella-a new threat to neonates - Begum, SA; Lutfor, AB; Mollah, AH; Hasan, MK; Ahmed, S; Akhter, M; Salauddin, NM (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2007 Jul;16(2 Suppl):S15-18 The abstract of this article is available on the PubMed website